PENGUATAN NILAI MODERASI BERAGAMA MELALUI PENDIDIKAN AGAMA ISLAM DI SMA NEGERI 7 SAMARINDA - Asria Ramadhani; Muthia Umi Setyoningrum (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2023)
Presently, the tendency of intolerance and radicalism among students is still quite worrying. Strengthening the value of religious moderation in schools is one of the steps to prevent radicalism and intolerance. This research is descriptive qualitative type. Research information comes from school principals, Islamic religious education teachers, and several Muslim students. Data was obtained or collected using interviews, documentation, and observation. The data analysis technique is the Miles, Huberman, and Saldana models. The data validity technique uses technique and source triangulation. The results showed several forms of activity at SMA N 7 Samarinda to strengthen the value of religious moderation, namely strengthening material on tolerance and unity in diversity in PAI lessons, Qur'an literacy, tausiyah day, Qur'an day, and PHBI activities. The form of strengthening for all religions is by giving messages related to tolerance at flag ceremonies, facilitating rooms and religious teachers for each religion, and equalizing treatment in organizations where they can learn to respect and respect each other's differences. The strengthening process is carried out by providing an in-depth understanding of tolerance and mutual respect through related materials and through activities that refer to a religion that is rahmatan lil 'alamin. The supporting factors are the participation of school principals and teachers in religious moderation activities, having a forum for strengthening the value of moderation, adequate facilities and infrastructure, and an instilled attitude of mutual respect and respect. The inhibiting factor is the lack of time to carry out activities to strengthen the value of religious moderation. But of course, a social attitude is felt, namely fairness, balance, tolerance, and embedded national commitment.